CARE program: NCI and FDA interagency collaborations to support oncology small business entrepreneurs. Issue 3 (22nd January 2023) - Pond, Monique A.; Narayanan, Deepa; Zhang, Kehui; Fau, Danielle; Summers, Jeffrey; Carranza, Dorn; Weingarten, Michael
Abstract: The National Cancer Institute's Small Business Innovation Research Development Center (NCI SBIR) supports the commercialization of novel cancer‐related technologies by providing resources to 300–400 small businesses each year. Whereas Federal funding is crucial for the translation of technologies to the clinic, the majority of these technologies will need to undergo regulatory review to reach clinical testing. Many small businesses find navigating their regulatory pathway challenging, largely due to lack of regulatory expertise on small startup teams with limited revenue. In collaboration with the US Food and Drug Administration (FDA), NCI SBIR launched a new regulatory assistance program called Connecting Awardees with Regulatory Experts (CARE). The goal of the CARE program is to connect NCI‐funded small businesses with the FDA to receive feedback on their regulatory questions during early‐stage product development. The program has a multipronged support approach and also educates companies about the FDA process and existing resources. To date, 141 companies have participated in the interagency program. Follow‐up surveys indicate that the program guided the companies in planning the next regulatory steps for their technology development (89%) and provided critical information that changed their future NCI small business grant project aims (81%). Overall, companies reported they would recommend the program to other companies (90%). This paper will discuss the CARE program outcomes as well as other NCI and FDA collaborations that support early‐stage small businesses, including the joint development of funding opportunities and online resources that focus on the oncology startup community.